Turkish version of the revised neurophysiology of pain questionnaire: reliability and an investigation on the pain neurophysiology knowledge in Turkish physiotherapy students - Secer, Erhan; Ozer Kaya, Derya (Physiotherapy theory and practice, 2025)
The aim of this study was to examine the reliability of the Turkish version of the revised Neurophysiology of Pain Questionnaire (RNPQ-TR) among Turkish physiotherapy (PT) students and to investigate their pain neurophysiology knowledge. A total of 448 PT students were included in the study. An online survey created using Google Forms was sent to the students via a link through messaging apps. The first-round of the online survey included the RNPQ-TR and questions about individual and academic characteristics. For reliability of the RNPQ-TR, the online survey included the RNPQ-TR was sent to the students ( = 159) to participate in a second-round. For RNPQ-TR, the Cronbach's α coefficient was 0.57 and ICC was 0.71 (95% CI 0.63 to 0.78). The SEM and MDC were 0.99 and 2.74, respectively. First-grade students' pain neurophysiology knowledge was lower than students in other grades ( = .035). Students who took lesson about pain as part of PT education had higher pain neurophysiology knowledge ( = .015). Students answered questions about the biological mechanisms underpinning pain at a higher rate, while they answered questions about how and why pain is perceived at a lower rate in this study. The RNPQ-TR had low internal consistency and moderate test-retest reliability. Turkish PT students' pain neurophysiology knowledge varied according to academic characteristics. There was a general tendency for Turkish PT students to have insufficient knowledge about how and why pain is perceived. We recommend the development and implementation of strategies to enhance Turkish PT students' pain neurophysiology knowledge.